A periplasmic phospholipase that maintains outer membrane lipid asymmetry in Pseudomonas aeruginos - Guest, Randi L.; Lee Michael J.; Wang, Wei; Silhavy, Thomas J. (My University, 2023)
The outer membrane of Gram-negative bacteria is unique in both structure and function. The surface-exposed outer leaflet is composed of lipopolysaccharide, while the inner leaflet is composed of glycerophospholipids. This lipid asymmetry creates mechanical strength, lowers membrane permeability, and is necessary for virulence in many pathogens. Glycerophospholipids that mislocalize to the outer leaflet are removed by the Mla pathway, which consists of the outer membrane channel MlaA, the periplasmic lipid carrier MlaC, and the inner membrane transporter MlaBDEF. The opportunistic pathogen Pseudomonas aeruginosa has two proteins of the MlaA family: PA2800 and PA3239. Here, we show that PA2800 is part of a canonical Mla pathway, while PA3239 functions with the putative lipase PA3238. While loss of either pathway individually has little to no effect on outer membrane integrity, loss of both pathways weakens the outer membrane permeability barrier and increases production of the secondary metabolite pyocyanin. We propose that mislocalized glycerophospholipids are removed from the outer leaflet by PA3239 (renamed MlaZ), transferred to PA3238 (renamed MlaY), and degraded. This pathway streamlines recycling of glycerophospholipid degradation products by removing glycerophospholipids from the outer leaflet prior to degradation.
Keywords: outer membrane; Mla pathway; PA2800; PA3238; PA3239